Kolaborasi Model Pentahelix: Studi Kasus pada Pengembangan Desa Wisata Berbasis Edukasi di Desa Doudo Kecamatan Panceng Kabupaten Gresik - Safitri, Lila Amelia; Nafi’ah, Binti Azizatun (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The Doudo Tourism Village is a tourism destination based on environmental education and agriculture in Gresik Regency. The development of an education-based tourism village in Doudo requires contributions from various parties through collaboration, in which Doudo Village adopts the Pentahelix collaboration model. The aim of this research is to describe the Pentahelix collaboration model in the development of an education-based tourism village in Doudo. This research is qualitative. Data collection techniques are carried out through observation, interviews, and documentation. Meanwhile, data analysis techniques consist of data collection, data condensation, data presentation, and drawing conclusions. The theory used is the Pentahelix collaboration model by Astuti et al. (2020), which includes: 1) Government, 2) Business Sector, 3) Universities, 4) Non-Governmental Organizations, and 5) Mass Media. The technique for determining informants in this research is purposive sampling, where the informants consist of the village head, staff of the BUMDes Among Swa Arta, community relations officer staff of PT Pertamina EP Poleng Field, head of the CSR and Empowerment Division of CARE IPB, secretaries and members of the agro-tourism group in Agro Edu Green Village, editors and journalists of Gresik Satu Media, and managers of the Doudo Eduwisata social media account. The results of the research show that there are 5 stakeholders involved in the development of an education-based tourist village in Doudo Village who have performed their duties well. There is a contribution from all parties to achieve the goals optimally. Each stakeholder has carried out their role according to their field. The success of this collaboration can be seen from the collaboration and synergy that have developed through interaction, coordination, and communication among stakeholders. Although there are still some obstacles in the development of the education-based tourist village in Doudo.